A literature review on the factors influencing employees' preference towards telecommuting - Ismail, Farah Diyanah; Kadar Hamsa, Abdul Azeez; Mohamed, Mohd Zin (2012)
Telecommuting is one of the possible solutions to several problems, especially traffic congestion, parking demand in large cities around the world. It is one of the transportation demand management measures to control increase in the travel demand by private vehicles during peak hours. It is apparent that the growth in the number of private vehicles in many Universities has been exerting tremendous pressure on the road infrastructure, parking supply and related traffic facilities. The increase in the number of private vehicle trips in International Islamic University Malaysia (IIUM) has made congestion during peak hours resulting in long queue of vehicles entering and leaving the campus, parking along the road side resulting in decrease in road capacity and increase in environmental damages. Physical extension of the road network to overcome the traffic problems is not always possible due to the limited availability of land space and other resources. Telecommuting is one of the potential measures to overcome the increasing number of private vehicles on-campus by allowing potential employees to telecommute especially at home. The possible adoption of telecommuting by potential employees is an area of concern before it can be considered for implementation. The purpose of this paper is to analyse literature on telecommuting aspects including factors contributing towards preference to telecommute.